2010
DOI: 10.1387/ijdb.103205sw
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of mouse cloning using nuclear transfer-derived embryonic stem cells and/or histone deacetylase inhibitor

Abstract: Nuclear transfer-derived ES (ntES

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…For this reason, many attempts to modify/improve SCNT efficiency have been reported (Iuso et al, 2013;Czernik et al, 2016). These improvements concerned the technical aspects (Wakayama et al, 2010, Czernik et al, 2016 as well as attempts as bulk or targeted modification of donor nucleus, before or af-et al, 2013). Those authors showed significantly higher blastocyst rates when SCNT was performed without exposure of the oocytes to UV, as compared to the traditional method.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, many attempts to modify/improve SCNT efficiency have been reported (Iuso et al, 2013;Czernik et al, 2016). These improvements concerned the technical aspects (Wakayama et al, 2010, Czernik et al, 2016 as well as attempts as bulk or targeted modification of donor nucleus, before or af-et al, 2013). Those authors showed significantly higher blastocyst rates when SCNT was performed without exposure of the oocytes to UV, as compared to the traditional method.…”
Section: Introductionmentioning
confidence: 99%
“…Embryonic stem cells derived from cloned embryos (ntESCs) have been established in mouse [14], human [24][25][26], and cattle [27]. In addition, it has been reported that the success rate of cloning was higher when mouse ESCs were used as a source of donor cells compared to more differentiated somatic cells, which are more resistant to epigenetic reprogramming [13,[28][29][30] Contrary to our expectation, the green fluorescent protein following piPSC-nt was expressed in the entire blastocyst rather than just in the ICM. In other words, it was also in the trophoblast.…”
Section: Discussionmentioning
confidence: 99%
“…Tail tips derived from mouse ConJ12 (fresh sample) or ConB23 (frozen sample with cell cryopreservation medium "CELLBANKER 1 plus"; Zenoaq) were cultured on a Petri dish for 12-14 d. The cultured tail-tip fibroblasts were used as nuclear donors. After nuclear transfer, the reconstructed oocytes were activated using 5 mM SrCl 2 in Ca-free CZB medium in the presence of 5 ÎŒM latrunculin A supplemented with trichostatin A (50 nM) for 9 h. After three washes in CZB, cloned embryos were cultured for 4 d in the same medium, and morula-or blastocyst-stage embryos were used to establish ntES cell lines as described previously (Wakayama et al 2001;Wakayama and Wakayama 2010).…”
Section: Nuclear Transfer and Establishment Of Ntes Cell Linesmentioning
confidence: 99%